PROBLEMS IN TAXATION IN FAVOR OF LEGAL ENTITIES IN UZBEKISTAN AND WAYS TO SOLVE THEM THROUGH THE EXPERIENCE OF FOREIGN COUNTRIES - Samadov, Shokhrux (Journal of Contemporary World Studies, 2024)
The article describes the main directions of tax policy in the conditions of rapid economic development and increasing the investment attractiveness of the country, consistent reduction of the tax burden, simplification of the taxation system and improvement of tax administration. At the same time, a number of systemic problems have been identified in this area that hinder economic growth, increase business and investment activity, the formation of a healthy competitive environment, as well as ensuring the necessary level of tax and other mandatory fees and specific recommendations and conclusions on tax simplification legislation in connection with the widespread introduction of modern information and communication technologies is scientifically justified.